Nodavirus replication in a turbot cell line - Aranguren, Raquel; Tafalla, Carolina; Novoa, Beatriz; Figueras Huerta, Antonio (Journal of Fish Diseases, 2002)
6 páginas, 3 figuras This research was partially supported by the Commission of the European Communities, Agriculture and Fisheries (FAIR) specific RTD programme CT97-3308. Peer reviewed